Assessing the effects of training and development on employee performance: a study of cocoa marketing company (gh) limited, Kumasi - Tweneboah-Koduah, Darling Abena (KNUST, 2025)
A THESIS SUBMITTED TO THE DEPARTMENT OF SOCIOLOGY AND SOCIAL WORK, IN PARTIAL FULFILMENT OF THE REQUIREMENTS FOR THE DEGREE OF (HONS), MA. SOCIOLOGY